Analisis Kemampuan Komunikasi Matematika Siswa Kelas X Fase E.1 pada Materi SPLDV - Suci Dela Roza; Muhammad Imamuddin; Liza Hamas (Department of Master Program on Mathematics Education Faculty of Teacher Training and Education State Islamic Institute of Lhokseumawe, Indonesia, 2023)
The aim of the research is to analyze students' mathematical communication. The research method used is descriptive qualitative at SMAN 1 HARAU. The sample used was 5 students randomly selected from class X phase E.1. Data collection methods in this study used tests of mathematical understanding using class written tests, and student interviews. The results of this study are that the mathematical communication skills of students in class X phase E.1 in SPLDV material are still in the low category. This can be seen from the results of the percentage scores obtained from the 4 items that have been given, where there are 2 items categorized as low with a presentation size less than 33%, and 2 items categorized as medium with a large percentage more than 33%. As well as students still having difficulty answering story questions in indicators of changing the form of story questions into mathematical models and solving them.